Penguatan Pendidikan Karakter Melalui Edukasi Literasi Keuangan untuk Remaja Sekolah Menengah - Faizal Rizky Yuttama; Budi Widadi (ARDHI : Jurnal Pengabdian Dalam Negri, 2025)
The purpose of this community service activity is to improve the knowledge of SMA Islam Andalusia Banyumas students about finance and teach them to use money wisely and independently starting from adolescence. The results showed that most students did not understand the basic concepts of financial literacy, such as the difference between needs and wants, budgeting, and the importance of saving. The training was conducted in one day with a participatory education approach. This method includes providing materials, group discussions, budgeting simulations, and individual reflections. This activity was attended by 80 students. The assessment results showed an increase in the average score from 52.4 in the pretest to 81.1 in the posttest. This activity also showed high active participation, with more than 88% of students actively involved in discussions and group assignments. This training proves that an experience-based approach can effectively improve students' understanding and awareness of personal financial management. Financial literacy instilled since high school has the potential to form a character of thrift, responsibility, and independence in facing future financial challenges